Poster 161: Consequence Athletes with Anterior Shoulder Instability: Consider Latarjet. Issue 7 (30th July 2022) - Hackett, Thomas; Provencher, Matthew; Millett, Peter; Woolson, Thomas; Horan, Marilee; Peebles, Annalise; Waltz, Robert
Objectives: The Latarjet procedure has been shown to be effective in treating recurrent shoulder instability, especially in the setting of glenoid bone loss and after failed previous Bankart repair. Several studies have additionally shown a significant reduction in recurrent instability rates when compared to Bankart repair in contact athletes when the Latarjet procedure is performed in a primary setting. We have identified an additional population of patients that provides greater challenges beyond the common athlete including those involved in contact sports. Termed "consequence athletes, " these patients are defined as athletes who perform in high risk, uncontrolled environments for whom an injury is likely to threaten life or livelihood. This population includes elite military forces, law enforcement and federal agents, motocross, elite skiers/snowboarders, whitewater kayak and rafters, and rock climbers. The purpose of this study is to evaluate minimum 2-year outcomes of primary Latarjet procedure in consequence athletes with anterior shoulder instability. Methods: Consequence athletes who underwent open Latarjet by one of the three sports medicine trained senior surgeons between August 2006 and January 2018 were retrospectively reviewed from prospectively collected data. Minimum 24 follow up was obtained on all patients. Those younger than 18 at follow up, history of concomitant or prior remplissage procedure, glenoid reconstruction with allograft, severe glenohumeral arthritis, or hyperlaxity were excluded. Glenoid bone loss (GBL) was evaluated on preoperative MRI and the cohort divided into GBL 0-14% and ≥15%. Patient-reported outcome scores (PROs) were collected and included the American Shoulder and Elbow Surgeons (ASES) score, Single Numeric Assessment Evaluation (SANE) score, Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) score, Short Form–12 (SF-12) Physical Component Summary (PCS), and numeric rating scale (NRS) for pain score (0 - 10, 10 = worst pain). Postoperative patient satisfaction (1 - 10, 10 = very satisfied) was evaluated. Complications and revision surgeries were recorded. Failure was defined as a postoperative dislocation or a revision surgery. Results: Sixty-five consequence athletes were included (54 males, 11 females). The mean age at surgery was 28.5 ± 8.7 years (range 15.8-56.4). The most frequent professions included 17 skiers (26.2%), 17 rock climbers (26.2%), 10 snowboarders (15.4%), 9 white water kayakers/rafters (13.8%), and 8 federal agents/military (12.3%). Primary latarjet was performed in 30 (46.2%) without prior history of soft tissue stabilization procedures. Mean GBL was 13.7%; 27 (41.5%) had 0-14% GBL and 32 (49.2%) had ≥15% GBL. Significant improvement in PROs at minimum 2-year follow was demonstrated for SANE (57.9 ± 24.5 to 91.0 ± 9.5), SF12 PCS (45.5 ± 8.7 to 54.4 ± 7.1), ASES pain (41.5 ± 9.7 to 47.4 ± 5.3), ASES function (31.8 ± 12.6 to 46.2 ± 6.8), ASES total (73.0 ± 19.8 to 93.7 ± 10.0), and quickDASH (27.0 ± 14.0 to 10.0 ± 28.8). Median patient satisfaction was 10. One patient sustained a recurrent dislocation (1.5%), 2 (3%) patients underwent revision surgery. There was no significant correlation between PROs and GBL, number of previous dislocations, or prior soft tissue stabilization procedures. Conclusions: The latarjet procedure a reliable and safe treatment for shoulder instability in the high demand "consequence athlete" population with a post-operative dislocation rate of 1.5% and revision rate of 3%. Significant improvement in PROs was demonstrated for SANE, SF12 PCS, ASES, and DASH with median patient satisfaction score of 10. These findings support treatment of this population with the latarjet procedure, even in the setting of minimal preoperative GBL, where a recurrent instability event could be catastrophic to the individual patient or those working or participating along with them.